Development of a pain education resource for people with spinal cord injury - Widerström-Noga, Eva; Anderson, Kimberly D.; Robayo, Linda E.; Perez, Salome; Martinez-Arizala, Alberto; Calle-Coule, Lindsey; Cherup, Nicholas P.; Fernandez, Gabriel E. (Frontiers in Public Health, 2023)
Many people with spinal cord injury (SCI) develop chronic pain, including neuropathic pain. Unfortunately, current treatments for this condition are often inadequate because neuropathic pain after SCI is complex in that it depends on many different underlying mechanisms and contributing factors. Multimodal treatment strategies including but not limited to pharmacological, physical, cognitive approaches, and pain education may be best suited to manage pain in this population. In this study, we developed an education resource named SeePain based on published pain literature, and direct stakeholder input, including people living with SCI and chronic pain, their significant others, and healthcare providers with expertise in SCI. The SeePain was then systematically evaluated by stakeholders regarding its content, comprehensibility, and format using thematic analysis to organize their perspectives and optimize its relevance. The final resource is a comprehensive guide for people with SCI and their significant others or family members that is intended to increase health literacy and facilitate communication between SCI consumers and their healthcare providers. The ultimate purpose of the SeePain is to help people with SCI to make pain manageable and reduce the negative impact of pain on quality of life after SCI.